Investigating the influence of micro-scholarship on emotional well-being and self-efficacy of students to achieve a sustainable goal - Ali, Imanat; Zuraina, Ali; Younus, Muhammad (The University of Lahore, 2025)
Education is needed for every child to cope with the world. However, it is a challenge for the low-income communities to educate children from the primary level. Therefore, micro-scholarship programs can play a vital role in providing education to less privileged students. This study focused on education as a sustainable goal to improve the emotional well-being and self-efficacy at the school level in Chakothi, Azad Kashmir. The study’s main goal was to examine the effect of micro-scholarship on students’ self-efficacy and emotional well-being and to investigate the perspectives and experiences of the students through a questionnaire and careful observation. By the examination of individual cases and perceptions, the research sought to provide a comprehensive and contextualized understanding of the participants’ experience. The population of the study consisted of 58 schools’ students who have been receiving books, stationery, and uniforms since 2022. The qualitative data results revealed that micro scholarship creates emotional stability, helps to build self-confidence as well as goal setting and achievement. Furthermore, it reduces the academic stress of the students. The quantitative data findings also supported qualitative outcomes such as mean value (Mean=3.81- 4.50) around 4, mode value (Mode 4-5) above 4 and the standard deviation under one ( SD=0.50 - 0.90) indicated great values of agreement as well as satisfaction of the students. The findings suggested a learning environment for underprivileged and in need students. It also determined scholars' fresh perspective when examining the connection between micro-scholarship and self-efficacy. Research Study provided a path forward for humanitarian-based initiatives that take into account the accomplishments and emotional well-being of the students.